EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10893092 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1020 ZenodoArchiveConcept: 10893091
Keywords: _r:AddedByMyEducationEvidence

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13766685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1059 ZenodoArchiveConcept: 13766684
Keywords: _r:AddedByMyEducationEvidence